In vivo chloride concentrations surge to proteotoxic levels during acid stress. (November 2018) - Stull, Frederick; Hipp, Hannah; Stockbridge, Randy; Bardwell, James
Abstract To successfully colonize the intestine, bacteria must survive passage through the stomach. The permeability of the outer membrane renders the periplasm of Gram-negative bacteria vulnerable to stomach acid, which inactivates proteins. Here we report that the semipermeable nature of the outer membrane allows the development of a strong Donnan equilibrium across this barrier at low pH. As a result, when bacteria are exposed to conditions that mimic gastric juice, periplasmic chloride concentrations rise to levels that exceed 0.6 M. At these chloride concentrations, proteins readily aggregate in vitro. The acid sensitivity of strains lacking acid-protective chaperones is enhanced by chloride, suggesting that these chaperones protect periplasmic proteins both from acidification and from the accompanying accumulation of chloride. These results illustrate how organisms have evolved chaperones to respond to the substantial chemical threat imposed by otherwise innocuous chloride concentrations that are amplified to proteotoxic levels by low-pH-induced Donnan equilibrium effects. Protonation of periplasmic protein carboxylic groups creates a Donnan equilibrium in the bacterial periplasmic space at low pH, leading to accumulation of Cl− and unfolding and aggregation of periplasmic proteins, which can be rescued by chaperones.